Positioning of iris in an ocular prosthesis: A systematic review - Seema Sathe; Sweta Pisulkar; Sharayu Vinod Nimonkar; Vikram Belkhode; Anjali Borle (Wolters Kluwer Medknow Publications, 2020)
Aim: To evaluate different methods, techniques, and concepts documented in the literature to assess iris positioning accurately to the related dimensions needed to effectuate maxillofacial rehabilitation of ocular prosthesis. Settings and Design: This systematic review was conducted as per the PRISMA guidelines which is the most opted reporting protocol. Materials and Methods: Two electronic databases PubMed and Cochrane Library) were searched for manuscripts published from 1969 till September 30, 2019. An electronic search (of peer review restricted to English language dental literature was conducted to identify the relevant scientific article on iris positioning in maxillofacial prostheses. Two observers independently read the abstracts and selected 17 full text articles fulfilling the inclusion criteria. Statistical Analysis Used: No meta-analysis was conducted due to heterogeneity of data obtained. Results: All the 17 documented articles related to determination of the iris positioning to perform maxillofacial prosthetic rehabilitation depicting the use of a strip of plastic template, a Boley's gauge, a millimeter ruler, a pupillometer, window light, an ocular locator with fixed caliper, inverted anatomic tracings, a transparent graph grid were reviewed systematically. Conclusion: Currently, there is no evidence in the form of a systematic review of the available literature discussing the best technique available for perfectly matching the iris positioning. However, the latest techniques making use of digital technology such as digital photography, is believed to be more precise for iris positioning in the ocular prosthesis.